YOUNG, L. & C. HARRISON. Systemic Functional Linguistics and Critical Discourse Analysis : studies in social change. London: Continum, 2004. 306p. - Resende, Viviane de Melo (Cadernos de Linguagem e Sociedade, 2010)
YOUNG, L. & C. HARRISON. Systemic Functional Linguistics and Critical Discourse Analysis : studies in social change. London: Continum, 2004. 306p.